2017
DOI: 10.3892/ol.2017.6511
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer requires multidisciplinary treatment to improve patient survival: A case report

Abstract: Abstract. The present study reports two cases of lung cancer with the involvement of the pleura. The diagnosis of adenocarcinoma with epidermal growth factor receptor (EGFR) mutation was made following repeated thoracentesis with cytology of pleural fluid and thoracoscopy with pleural biopsies. Talc pleurodesis was successfully performed in both cases subsequent to diagnosis. Following talc pleurodesis, the first patient (62 years old; male; non-smoker) underwent 3 cycles of cisplatin/vinorelbine chemotherapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…As far as surgery techniques is concerned one possible approach in lung cancer surgery treatment is the video assisted thoracoscopy (VATS) approach that has a signi cantly lower rate of complications compared with thoracotomy (28% vs 45%, p = 0.04) (24).Other valid approaches that we used are minithoracotomy or lateral muscle sparing thoracotomy suitable for different extent of resection. Our study is the result of an interdisciplinary cooperation notably between pulmonologist and thoracic surgeon allows to better manage the patient undergoing lung cancer treatment consistently with previous studies (25)Greater loss of function in the sense of a decrease of FEV1 and FVC was observed in patients treated with lobectomy leading to a greater lung failure percentage and longer hospitalization time. A recovery from lung failure after three months along with a lower hospitalization time was observed notably in patients treated with sub-lobar resection.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As far as surgery techniques is concerned one possible approach in lung cancer surgery treatment is the video assisted thoracoscopy (VATS) approach that has a signi cantly lower rate of complications compared with thoracotomy (28% vs 45%, p = 0.04) (24).Other valid approaches that we used are minithoracotomy or lateral muscle sparing thoracotomy suitable for different extent of resection. Our study is the result of an interdisciplinary cooperation notably between pulmonologist and thoracic surgeon allows to better manage the patient undergoing lung cancer treatment consistently with previous studies (25)Greater loss of function in the sense of a decrease of FEV1 and FVC was observed in patients treated with lobectomy leading to a greater lung failure percentage and longer hospitalization time. A recovery from lung failure after three months along with a lower hospitalization time was observed notably in patients treated with sub-lobar resection.…”
Section: Discussionsupporting
confidence: 80%
“…The overall data were: mean age 71.5, hospitalization time 7.8 days, pack-year 34, body mass index (BMI) 25.4, chronic obstructive pulmonary disease(COPD) assessment test (CAT) mean value was 16.5, forced expiratory one second volume (FEV1) at baseline 1.6 l corresponding to 73.6% of predicted.…”
Section: Resultsmentioning
confidence: 99%
“…Desafortunadamente, en pa铆ses como Colombia los tr谩mites administrativos pueden hacer del proceso diagn贸stico un camino largo y tortuoso, por lo que se vuelve indispensable crear estrategias locales rentables, eficaces, eficientes, multidisciplinarias, al alcance de los pacientes y con evidencia suficiente para adelantar y priorizar los estudios de detecci贸n temprana, caracterizaci贸n y estratificaci贸n de c谩ncer de pulm贸n tales como marcadores de inmunohistoqu铆mica y pruebas moleculares espec铆ficos basados en los hallazgos fibrobroncosc贸picos e histol贸gicos. [28][29][30][31] Esto permitir铆a realizar un diagn贸stico oportuno y por consiguiente dar un tratamiento dirigido en un menor tiempo.…”
Section: Resultsunclassified
“…The techniques followed the American Thoracic Society and European Respiratory Society task force guidelines (5). sub-analysis included a group who underwent lobectomy (25) and group with sub-lobar resection (40)…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the video assisted thoracoscopy (VATS) approach has a signi cantly lower rate of complications compared with thoracotomy (28% vs 45%, p = 0.04) with a lower hospitalization time (24).Our approach consisted of either mini-thoracotomy or lateral muscle sparing thoracotomy suitable for different extensive resection. Further consideration is that the interdisciplinary cooperation notably between pulmonologist and thoracic surgeon allows to better manage the patient affected by lung cancer as demonstrated by previous studies (25)Greater loss of function in the sense of a decrease of FEV1 and FVC was observed in patients treated with lobectomy leading to a greater lung failure percentage and longer hospitalization time. A recovery from lung failure after three months along with a lower hospitalization time was observed notably in patients treated with sub-lobar resection.…”
Section: Copd and Lung Cancer Have A Common Origin Sharing In Ammatiomentioning
confidence: 97%